Was erleichtert, was hemmt die Zuwanderung polnischer Ärzte: Analyse ihrer Migrationsentscheidung und der relevanten deutschen Zuwanderungspolitik - Simon Fellmer (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
– In Germany two radical changes have recently been made in immigration policy. First the free movement of labour was stopped with regard to the EU accession country of Poland, secondly the immigration act was passed. Based on the concrete example of Polish doctors' decisions to immigrate, this paper asks whether these legal developments are in accordance with Germany's needs. The immigration of doctors is identified as a need on the basis of economic studies and a discussion of the extent and development of the shortage of doctors. Consequently the immigration of Polish doctors is (also) desirable. By means of the theory of wage differentials, the incentives are portrayed that lead these doctors to immigrate into Germany for economic reasons. Then the obstacles that prevent people from emigrating are described. The paper looks into which amendments of the law hinder or encourage the decision. It emerges that the majority of the amendments that can encourage migration originate from European initiatives, whilst the amendments in the genuinely German legislation promise a more marginally positive impact.
Keywords: 330; Arzt; Einwanderungspolitik; Pole; ausländische Arbeitnehmer; Mobilitätsbereitschaft - Determinanten; internationale Wanderung